Control of hmu Heme Uptake Genes in Yersinia pseudotuberculosis in Response to Iron Sources - Schwiesow, Leah; Mettert, Erin; Wei, Yahan; Miller, Halie K.; Herrera, Natalia G.; Balderas, David; Kiley, Patricia J.; Auerbuch, Victoria (Frontiers in Cellular and Infection Microbiology, 2018)
Despite the mammalian host actively sequestering iron to limit pathogenicity, heme (or hemin when oxidized) and hemoproteins serve as important sources of iron for many bloodborne pathogens. The HmuRSTUV hemin uptake system allows Yersinia species to uptake and utilize hemin and hemoproteins as iron sources. HmuR is a TonB-dependent outer membrane receptor for hemin and hemoproteins. HmuTUV comprise a inner membrane ABC transporter that transports hemin and hemoproteins from the periplasmic space into the bacterial cytoplasm, where it is degraded by HmuS. Here we show that hmuSTUV but not hmuR are expressed under iron replete conditions, whereas hmuR as well as hmuSTUV are expressed under iron limiting conditions, suggesting complex transcriptional control. Indeed, expression of hmuSTUV in the presence of inorganic iron, but not in the presence of hemin, requires the global regulator IscR acting from a promoter in the intergenic region between hmuR and hmuS. This effect of IscR appears to be direct by binding a site mapped by DNaseI footprinting. In contrast, expression of hmuR under iron limiting conditions requires derepression of the ferric uptake regulator Fur acting from the hmuR promoter, as Fur binding upstream of hmuR was demonstrated biochemically. Differential expression by both Fur and IscR would facilitate maximal hemin uptake and utilization when iron and heme availability is low while maintaining the capacity for periplasmic removal and cytosolic detoxification of heme under a wider variety of conditions. We also demonstrate that a Y. pseudotuberculosis ∆iscR mutant has a survival defect when incubated in whole blood, in which iron is sequestered by heme-containing proteins. Surprisingly, this phenotype was independent of the Hmu system, the type III secretion system, complement, and the ability of Yersinia to replicate intracellularly. These results suggest that IscR regulates multiple virulence factors important for Yersinia survival and growth in mammalian tissues and reveal a surprising complexity of heme uptake expression and function under differing conditions of iron.